2022
DOI: 10.1002/advs.202204247
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Exfoliation Method for Plasmonic Activation of Large‐Area 2D Crystals

Abstract: Advanced exfoliation techniques are crucial for exploring the intrinsic properties and applications of 2D materials. Though the recently discovered Au‐enhanced exfoliation technique provides an effective strategy for the preparation of large‐scale 2D crystals, the high cost of gold hinders this method from being widely adopted in industrial applications. In addition, direct Au contact could significantly quench photoluminescence (PL) emission in 2D semiconductors. It is therefore crucial to find alternative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Meeting condition (1) in air or inside glove box environment is problematic because of the requirement for exfoliation to be performed immediately after metallic surface evaporation, and because most ex vacuo surfaces will quickly undergo chemistry or adsorption of impurities, even in a glovebox. Recent work has shown that the Ag substrate exhibits a similar exfoliation yield as Au, [ 76 ] but the observed efficiency declines rapidly within ≈10 s due to surface oxidation. This effect limits the possible choice of substrate to relatively non‐reactive Au or Ag and makes the exfoliation technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Meeting condition (1) in air or inside glove box environment is problematic because of the requirement for exfoliation to be performed immediately after metallic surface evaporation, and because most ex vacuo surfaces will quickly undergo chemistry or adsorption of impurities, even in a glovebox. Recent work has shown that the Ag substrate exhibits a similar exfoliation yield as Au, [ 76 ] but the observed efficiency declines rapidly within ≈10 s due to surface oxidation. This effect limits the possible choice of substrate to relatively non‐reactive Au or Ag and makes the exfoliation technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…42 Recently, a one-step Ag-assisted method has been developed by Huang et al that efficiently exfoliates many large-area 2D monolayers. 43 The yield ratio of this method is comparable to that of the Au-film-assisted exfoliation method. However, it is worth noting that the surface roughness of Ag films on SiO 2 /Si substrates is higher compared to Au films.…”
mentioning
confidence: 82%
“…as an intermediary layer. 32,43 Finding a cheaper intermediary material that can achieve high-quality and largearea exfoliation is an area that requires further exploration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are usually prepared by mechanically assisted exfoliation, ion intercalation/sonification-assisted liquid exfoliation, and chemical vapor deposition (CVD). [28][29][30][31][32] In contrast, nonlayered materials typically include ultrathin nanosheets of metal and metal oxides, are usually known as 3D bulk crystals connected by strong chemical bonds. However, they are limited in one direction to form 2D nanosheet structures during crystallization.…”
Section: Structure Of 2d Materials Catalystsmentioning
confidence: 99%